Membaca Kebijakan Pendidikan di Indonesia dan Malaysia Terkait Tes PISA - Abdillah, Muhammad Torieq; Syifa, Siti Nur (Universitas Tribhuwana Tunggadewi, 2025)
This research is based on the results of the 2022 PISA test, which revealed that Indonesia's scores are still lower than Malaysia's, despite both countries emphasizing literacy in reading, mathematics, and science in their education policies, as outlined in their respective constitutions and laws. This study employs a descriptive- qualitative method with a comparative approach through literature review. The results of the study show that indicate a significant gap in the abilities of Indonesian and Malaysian students in reading literacy, mathematics, and science, as shown by the 2022 PISA results. Malaysian students excel due to a more stable curriculum, a progressive mindset, and strong socio-cultural support. In contrast, Indonesian students face challenges such as a fixed mindset, math anxiety, low scientific literacy, and ineffective teaching methods. However, Indonesia's new education policies bring hope for future improvements. Changes are needed, including fostering a positive mindset, stabilizing the curriculum, implementing innovative teaching methods, and enhancing teacher quality.Collaboration among the government, schools, and families is crucial to creating a supportive learning environment, enabling Indonesian students to compete on an international level.Penelitian ini dilatar belakangi hasil tes PISA 2022 yang mana hasil skor Indonesia masih kalah unggul dari Malaysia yang saat bersamaan memiliki semangat pendidikan melalui kebijakan pendidikan yang sama dengan mengutamakan literasi membaca, matematika, dan sains yang dituangkan di konstitusi dan peraturan perundang-undangan masing-masing negara. Penelitian ini menggunakan teknik komparatif untuk mengkaji literatur dan bersifat deskriptif-kualitatif. Hasil penelitian ini menunjukkan bahwa melalui hasil tes PISA 2022 terdapat kesenjangan signifikan antara kemampuan siswa Indonesia dan Malaysia dalam literasi membaca, matematika, dan sains. Siswa Malaysia unggul karena kurikulum yang lebih stabil, mindset yang progresif, serta dukungan sosial-budaya yang kuat. Sebaliknya, siswa Indonesia menghadapi tantangan seperti fixed mindset, kecemasan terhadap matematika, rendahnya literasi sains, dan metode pembelajaran yang kurang efektif. Namun, kebijakan pendidikan baru di Indonesia membawa harapan untuk perbaikan pada masa depan. Perubahan diperlukan, termasuk pengembangan mindset positif, stabilisasi kurikulum, metode pembelajaran inovatif, dan peningkatan kualitas guru. Kolaborasi antara pemerintah, sekolah, dan keluarga sangat penting untuk menciptakan lingkungan belajar yang mendukung agar siswa Indonesia mampu bersaing di tingkat internasional.